Immunovirological Analyses of Chronically Simian Immunodeficiency Virus SIVmnd-1- and SIVmnd-2-Infected Mandrills (Mandrillus sphinx) - Apetrei, Cristian (American Society for Microbiology, 2011)

(untitled)
Simian immunodeficiency virus (SIV) infection in African nonhuman primate (NHP) natural hosts is usually nonpathogenic, despite high levels of virus replication. We have previously shown that chronic SIV infection in sooty mangabeys (SMs) and African green monkeys (AGMs) is associated with low levels of immune activation and bystander T cell apoptosis. To compare these features with those observed in another natural host, the mandrill (MND), we conducted a cross-sectional survey of the 23 SIV-infected and 25 uninfected MNDs from the only semifree colony of mandrills available worldwide. Viral loads (VLs) were determined and phenotypic and functional analysis of peripheral blood- and lymph node-derived lymphocytes was performed. We found that mandrills chronically infected with SIVmnd-1 or SIVmnd-2 have similar levels of viral replication, and we observed a trend toward lower CD4(+) T cell counts in chronically SIVmnd-2-infected MNDs than SIVmnd-1-infected MNDs. No correlation between CD4(+) T cell counts and VLs in SIV-infected MNDs could be established. Of note, the levels of T cell activation, proliferation, and apoptosis were comparable between SIVmnd-1- and SIVmnd-2-infected MNDs and to those observed in uninfected animals, with the only exception being an increase in tumor necrosis factor alpha-producing CD8(+) T cells in SIVmnd-2-infected MNDs. Overall, these findings recapitulate previous observations in SIV-infected SMs and AGMs and lend further evidence to the hypothesis that low levels of immune activation protect natural SIV hosts from disease progression.